Welfare parameters and keel bone damage in laying hens reared in different production systems - Spiridonović Sava (Institute for Animal Husbandry, Belgrade, 2021)
The aim of this study was to determine the effect of housing system and the age of hens on welfare parameters and the prevalence of keel bone damage in laying hens. In this study two housing systems were evaluated: aviary system and enriched cages. From each system and age, we used 50 randomly selected hens from different cages and tiers. The results showed significant differences between systems in the type of keel bone damage. There was no significant difference in keel deviation between systems, but the higher prevalence of keel fractures was found in aviary system. In addition, significant effect of the age of hens was found on the occurrence of keel fractures. Footpad dermatitis had statistically higher occurrence in enriched cages at 62 weeks of age. Hens from aviary system had significantly better plumage score compared to hens from enriched cages but only at 42 weeks of age.